1982
DOI: 10.1901/jaba.1982.15-191
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Training of Clinical Interviewing Skills: Analogue Analysis and Field Replication

Abstract: Two studies were conducted to assess and train clinical interviewing skills. In Experiment 1, eight university practicum students ("therapists") and either role played or volunteer "clients" were audiotaped during simulated interviews. Following the collection of baseline data on both therapist and client responses, training was provided by way of written materials, classroom instruction and practice, and quizzes. Results of a multiple baseline design across subjects showed improvements in therapists' intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
6

Year Published

1985
1985
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 18 publications
1
34
0
6
Order By: Relevance
“…Pre‐study functional analysis . Functional behavioral assessment interviews (adapted from Iwata, Wong, Riordan, Dorsey & Lau, 1982) and a functional analysis (Iwata, Dorsey, Slifer, Bauman and Richman (1982/1994) indicated that Andy's hair pulling was maintained by adult attention and Jackie's aggression was maintained by access to food. An interview and home visit suggested that Tom's food stealing was maintained by access to food.…”
Section: Methodsmentioning
confidence: 99%
“…Pre‐study functional analysis . Functional behavioral assessment interviews (adapted from Iwata, Wong, Riordan, Dorsey & Lau, 1982) and a functional analysis (Iwata, Dorsey, Slifer, Bauman and Richman (1982/1994) indicated that Andy's hair pulling was maintained by adult attention and Jackie's aggression was maintained by access to food. An interview and home visit suggested that Tom's food stealing was maintained by access to food.…”
Section: Methodsmentioning
confidence: 99%
“…For each participant, functional analysis conditions were randomly drawn and conducted in a multielement design. Prior to the formal functional analysis, the primary caregivers for both participants were interviewed using a structured behavioral interview (Iwata, Wong, Riordan, Dorsey, & Lau, 1982). In addition, the therapists conducted informal observations of the participants on the living unit.…”
Section: Phase 1: Functional Analysis Procedures and Designmentioning
confidence: 99%
“…The purpose of this experiment was to evaluate the effectiveness of an instructional manual that required no trainer involvement for the acquisition of behavioral assessment interviewing skills similar to those reported by Iwata et al (1982). The effectiveness of training manuals has been demonstrated in other areas such as conducting interdisciplinary meetings (Parrish, Iwata, & Johnston, 1985) and training respite care workers (Parrish, Neef, Egel, & Sloane, 1984).…”
Section: Preparation Of This Manuscript Was Supported In Part Bymentioning
confidence: 99%